Urgensi Mobile Learning Berbasis Situs Jejak Gerilya Jenderal Soedirman di Pakisbaru Pacitan sebagai Media Pembelajaran Sejarah Generasi Z - Maghfiroh, Aghnia Muzamilul; Suprapta, Blasisus; sulistyo, wahyu djoko (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research was conducted to analyze the urgency of history learning media innovation. The development of the times puts history learning to have challenges to be able to adapt the learning targets faced, namely the Z Generation. This generation was born in the early 2000s. The character of this generation is very sensitive to technology and communication, meaning that they have advantages in the field of information and knowledge. Meanwhile, educators who were born in the previous era are still didn't used to it, so that educators often admit to being